The implications of a changing value system for policy and practice of teacher education curriculum in Malaysia - Ratnavadivel, Nagendralingan; Nagappan, Rajendran; Dawi, Amir Hasan; Hin, Lim Chong (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Teacher education programmes the world over are based on national ideologies, policies and development plans. They are grounded in the culture of knowledge espoused by the major stakeholders (Bruner, 1996). The culture in turn is based on the value system espoused by the stakeholders concerned and this value system is incorporated and reflected in the teacher education programmes, particularly its curriculum and the management and development of the curriculum. A value system is in essence the ordering and prioritization of the ethical and ideological values that individuals or society hold. However, value systems are not something static. On the contrary they are dynamic and ever changing. In view of the emerging trends and challenges of globalization (Friedman, 2004), it has become necessary to view teacher education within the wider context of both the professional community and society at large. The state and nature of the rapid change requires teacher education to be more outward looking and be geared towards enabling teachers to be engaged in constant professional learning and self- improvement.